FACTORS OF POLITICAL PROFESSIONALIZATION AND THEIR INFLUENCE ON MUNICIPAL GOVERNANCE IN DISTRICT IV OF GUAYAQUIL - Patiño Guamán, Gabriel Alberto (2025)
The professionalization of politics and governance is essential for the development of effective, transparent and community-oriented democratic institutions The research analyzed the influence of political professionalization on municipal governance and governability in a district in Ecuador. The exploratory and descriptive qualitative methodology included semi-structured interviews with 12 key actors as a study sample, thematic analysis through coding and construction of semantic networks using Atlas.ti 24 software to code responses in categories such as professional integrity, corruption, transparency and accountability. The results show that while political professionalization can improve administrative efficiency and transparency, it faces challenges such as resistance to change and disconnection with citizen reality. Negative practices, such as influence peddling and money laundering, are critical obstacles to effective governance, while education and ethics training are essential components to strengthen the capacity of political actors. To ensure transparent and win-win governance, it is recommended that political professionals combine appropriate technical training with a solid ethical foundation.